(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2013)
We studied the coastal zooplankton community structure of six waterbodies of Mathbaria and Bakerganj from January 2008 to June 2009. In total 35 zooplankton species were identified under 26 genera under 20 families under 8 orders from Mathbaria. Among them 6 were protozoans, 24 were rotifers, 3 were copepods, 1 was cladocerans and 1 was ostracods. From Bakergonj a total of 42 zooplankton species were identified under 23 genera under 17 Families under 7 orders. Among them 3 were protozoans, 25 were rotifers, 7 were copepods, 6 were cladocerans and 1 was ostracods. Results showed that abundance of rotifera group from both area was higher in Mathbaria (64.86%) and Bakerganj (60.98%) than other groups while abundance of ostracoda of Bakerganj area was lowest. DOI: http://dx.doi.org/10.3329/jasbs.v38i1.15326 J. Asiat. Soc. Bangladesh, Sci. 38(1): 111-117, June 2012